Pengaruh Pemberian Posisi Head Up 30 Derajat Terhadap Saturasi Oksigen Pada Pasien Stroke Di Igd Rsud Dr. T.C. Hillers Maumere Kabupaten Sikka - Epiphania Trisila; Fransiska Aloysia Mukin; Melkias Dikson (Jurnal Ilmiah Wahana Pendidikan, 2022)
Stroke is a loss of brain function due to cessation or reduced blood supply to the brain, causing local or global nerve function disorders that arise suddenly, progressively, and rapidly. Blood flow that is not smooth in stroke patients can result in hemodynamic disturbances including oxygen saturation. One of the independent nursing actions to increase oxygen saturation is by giving a head up position of 30 degrees. The purpose of this study was to determine the effect of giving a 30 degree Head Up position on oxygen saturation in stroke patients. This type of research is quantitative research with a quasi-experimental research method with one group pre-test-post-test design. The number of samples in this study were 15 samples with accidental sampling technique. Data were collected using observation instruments. The results showed that 100% of the 15 respondents experienced a decrease in oxygen saturation, and 100% experienced an increase in oxygen saturation after giving the head up position 30 degrees. This study used the Wilcoxon statistical test which showed that giving the head up position 30 degrees had a significant effect in increasing oxygen saturation in stroke patients (p value = 0.000; = 0.05; and Z count = -3.493). There is an effect of giving a 30 degree head-up position on oxygen saturation in stroke patients in the emergency department of RSUD dr. T.C. Hillers Maumere. Recommendations from the study are aimed at nurses so that they can apply the provision of a 30 degree head up position as one of the independent nursing actions for stroke patients and to hospitals to prepare a 30 degree head up position SOP.